Problems of Public Administration in the United Territorial Communities in Ukraine - Savchenko, A. (Економічний вісник Донбасу, 2019)
An analysis of the existing united territorial communities (OTG) and the process of completion of their creation shows the presence of serious problems arising inside the OTG as a result of unequal initial conditions for their creation, and because of the unwillingness of their leadership to the new conditions of public administration within communities. It is shown that the traditional relations “society-personality”, “leadership-population” within the OTG are not correspond to the requirements that form the very nature of OTG as self-governing administrative units. The traditional manifestations of the people who are members of OTG related to their departure, work, shopping and using services in other OTGs lead to a decrease in the incomes of the OTGs in which they live, which determines the appearance of OTG-donors and OTG-recipients.
This makes it urgent to create a modern public administration system within communities that is able to recognize the causes of emerging problems, respond to them in a timely manner, prevent negative trends and encourage community members to work for the common good, including by allocating special budget funds for farming development and others types of entrepreneurship in OTG. Аналіз діючих об'єднаних територіальних громад (ОТГ) і процесу завершення їх створення показує наявність серйозних проблем, що виникають всередині ОТГ як через нерівномірність початкових умов їх створення, так і через неготовність їх керівництва до нових умов публічного управління всередині громад. Показано, що традиційні відносини «суспільство-особистість», «керівництво-населення» всередині ОТГ не відповідають вимогам, які формує сама природа ОТГ, як самоврядних адміністративних одиниць. Традиційні прояви людей-членів ОТГ, пов'язані з їх від'їздом, роботою, покупками і користуванням послугами в інших ОТГ, призводять до зменшення доходів ОТГ, в яких вони проживають, чим обумовлюється поява ОТГ-донорів і ОТГ-реципієнтів.
Це робить актуальним завдання формування сучасної системи публічного управління всередині громад, здатної усвідомлювати причини проблем, своєчасно на них реагувати і розробляти систему заходів запобігання негативним тенденціям і заохочення членів громад до праці на загальну користь, у тому числі за рахунок виділення спеціальних коштів бюджету на розвиток фермерства та інших видів підприємництва в ОТГ. Анализ действующих объединенных территориальных громад (ОТГ) и процесса завершения их создания показывает наличие серьезных проблем, возникающих внутри ОТГ как по причине неравномерных начальных условий их создания, так и из-за неготовности их руководства к новым условиям публичного управления внутри громад. Показано, что традиционные отношения «общество-личность», «руководство-население» внутри ОТГ не соответствуют требованиям, которые формирует сама природа ОТГ, как самоуправляемых административных единиц. Традиционные проявления людей-членов ОТГ, связанные с их отъездом, работой, покупками и пользованием услугами в других ОТГ, приводят к уменьшению доходов ОТГ, в которых они проживают, чем обусловливается появление ОТГ-доноров и ОТГ-реципиентов.
Это делает актуальной задачу формирования современной системы публичного управления внутри громад, способной осознавать причины возникающих проблем, своевременно на них реагировать и разрабатывать систему мер предотвращения негативных тенденций и поощрения членов общин к труду на общую пользу, в том числе за счет выделения специальных средств бюджета на развитие фермерства и других видов предпринимательства в ОТГ.